Marketing Practices and Consumer's Satisfaction in the Nigerian Banking Industry - Areo, Adebowale Biodun (2015)
The study evaluated the marketing policies, strategies and application of various marketing concepts in selected banks in Nigeria. It also assessed the competitive marketing strategies used in promoting the delivery of bank services and examined the corporate social responsibility in the banking industry with a view to determining their effect on consumers' satisfaction.